Specialized competency framework for pharmacists in managerial positions in sales and marketing (SCF-PMSM): development, validation, and correlates - Hala Sacre; Randa Aoun; Chadia Haddad; Carla Abou Selwan; Rony M. Zeenny; Marwan Akel; Aline Hajj; Carole Hassoun; Joya Namnoum; Katia Iskandar; Pascale Salameh (Taylor & Francis Group, 2023)
Abstract Background Pharmacists in sales and marketing roles need specific skills for managerial positions, and a framework for evaluating and developing these competencies is necessary. Currently, no such framework is known to exist. Objective This study aimed to develop and validate a specialized competency framework for pharmacists in sales and marketing managerial positions and assess correlates related to the competency domains. Methods This web-based study carried out between March and October 2022 enrolled a convenient sample of 60 pharmacists with managerial positions in sales and marketing, contacted by phone, working in the field of sales and marketing from the five governorates of Lebanon (Beirut, Beqaa, Mount Lebanon, South, and North). Results The framework demonstrated good construct and structural validity in all domains except for emergency preparedness, which had a low correlation with other domains. Competencies were well correlated with respective domains, and behaviors had excellent loadings on corresponding competencies. As for the correlates of the competency domains, males were more confident than females (p < .05), and participants with more experience (or heavier workload) reported higher competency levels (p < .05), particularly for upper management skills, communication skills, and professional practice. Further, education level was not significantly correlated with declared competency, with experience being the most cited source of competence (68.25%), followed by postgraduate degrees (42.48%) and continuing education sessions (33.93%), while undergraduate education was the least reported (29.5%). Conclusion This study could develop and validate the Specialized Competency Framework for Pharmacists in Managerial Positions in Sales and Marketing (SCF-PMSM) among a sample of Lebanese pharmacists. This framework demonstrated good reliability, content, construct, and structural validity in all the domains, with the competencies being well correlated with their respective domains and behaviors having excellent loadings on related competencies, except for emergency preparedness and response. It also revealed a mismatch between what is taught at undergraduate and postgraduate levels and the needs in practice.